Contested Ground: Disentangling Material and Symbolic Attachment to Disputed Territory. Issue 4 (12th June 2018) - Manekin, Devorah; Grossman, Guy; Mitts, Tamar
Abstract : Territorial disputes are prone to conflict because of the value of territory to publics, whether due to its strategic and material worth, or to its intangible, symbolic value. Yet despite the implications of the distinction for both theory and policy, empirically disentangling the material from the symbolic has posed formidable methodological challenges. We propose a set of tools for assessing the nature of individual territorial attachment, drawing on a series of survey experiments in Israel. Using these tools, we find that a substantial segment of the Jewish population is attached to the disputed West Bank territory for intangible reasons, consisting not only of far-right voters but also of voters of moderate-right and centrist parties. This distribution considerably narrows the bargaining space of leaders regardless of coalitional configurations. Our empirical analysis thus illustrates how the distribution of territorial preferences in the domestic population can have powerful implications for conflict and its resolution.